DINAMIKA CITRA CALON PRESIDEN RI 2024 DALAM KONTESTASI POLITIK - Syaifullah, Jahid; Agung Wibiyanto; Ali Arif Setiawan (Program Studi Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas Sumatera Selatan, 2024)
The political competition in Indonesia is quite dynamic and is also heating up towards 2024, especially from the competing candidates for the Indonesian presidency, such as Ganjar Pranowo, Prabowo Subianto and also Anies Baswedan. The purpose of this article is to review the dynamics of the image of the 2024 RI presidential candidate in political contestation. The method used is qualitative with descriptive analysis, where the data obtained is processed and reduced and analyzed to become an article. The findings state that the dynamics of the image of the 2024 Republic of Indonesia presidential candidate include personal images of Ganjar Pranowo, Prabowo Subianto and Anies Baswedan, images in issues of sustainability and issues of change, Anies Baswedan